Bidirectional Relationship Between Cardiac Extracellular Matrix and Cardiac Cells in Ischemic Heart Disease. (4th September 2021) - Park, Hyun-Ji; De Jesus Morales, Kenneth J.; Bheri, Sruti; Kassouf, Brandon P.; Davis, Michael E.
Abstract: Ischemic heart diseases (IHDs), including myocardial infarction and cardiomyopathies, are a leading cause of mortality and morbidity worldwide. Cardiac-derived stem and progenitor cells have shown promise as a therapeutic for IHD but are limited by poor cell survival, limited retention, and rapid washout. One mechanism to address this is to encapsulate the cells in a matrix or three-dimensional construct, so as to provide structural support and better mimic the cells' physiological microenvironment during administration. More specifically, the extracellular matrix (ECM), the native cellular support network, has been a strong candidate for this purpose. Moreover, there is a strong consensus that the ECM and its residing cells, including cardiac stem cells, have a constant interplay in response to tissue development, aging, disease progression, and repair. When externally stimulated, the cells and ECM work together to mutually maintain the local homeostasis by initially altering the ECM composition and stiffness, which in turn alters the cellular response and behavior. Given this constant interplay, understanding the mechanism of bidirectional cell-ECM interaction is essential to develop better cell implantation matrices to enhance cell engraftment and cardiac tissue repair. This review summarizes current understanding in the field, elucidating the signaling mechanisms between cardiac ECM and residing cells in response to IHD onset. Furthermore, this review highlights recent advances in native ECM-mimicking cardiac matrices as a platform for modulating cardiac cell behavior and inducing cardiac repair. : Our review focuses on the cardiac extracellular matrix (ECM) and cardiac fibroblasts (CFs), cardiac-derived progenitor cells (CPCs), and mesenchymal stem cells (MSCs), and their constant interplay in response to tissue development, aging, disease progression, and repair.